Metagenomic insights into short-term legume rotation: modulating potato rhizosphere microbiota to enhance tuber yield and quality - Shi, Mingfu; Guo, Aixia; Qin, Shuhao; Kang, Yichen; Zhang, Weina; Yang, Xinyu (Frontiers in Microbiology, 2026)
ObjectiveThis study aims to investigate the effects of legume crop rotation on the rhizosphere microbiota and its potential to improve potato (Solanum tuberosum L.) productivity and tuber quality. We specifically focus on the microbial functional potential revealed through metagenomic sequencing under different legume rotation systems in the intensive agricultural region of the Chinese Loess Plateau.MethodsA five-year field experiment (2018–2022) was conducted to establish three cropping systems: (1) continuous potato monocropping for 5 years (CK), (2) continuous potato cropping for 3 years followed by one-year pea rotation and one-year potato cropping (T1), and (3) continuous potato cropping for 3 years followed by one-year faba bean rotation and one-year potato cropping (T2). The impacts of these rotation regimes on potato yield formation, tuber quality, and rhizosphere microbial communities were systematically evaluated, with a focus on microbial diversity and functional potential, using metagenomic sequencing and network analysis.ResultsMetagenomic analysis demonstrated that legume rotation, particularly the T2 system, significantly enriched the relative abundances of Actinobacteria (38.31%) and Proteobacteria (28.40%) in the potato rhizosphere while reducing Acidobacteria (10.03%). Functional annotation further revealed that T2 promoted the expression of microbial genes involved in carbon fixation (K00626, K01895, etc.), nitrogen assimilation (narB, narA, etc.), and sulfur metabolism (cysNC, cysN, etc.), enhanced potential for nutrient cycling. Co-occurrence networks revealed Actinobacteria and Acidobacteria as keystone taxa forming robust interaction modules potentially linked to soil ecological stability. Compared to CK, T2 increased the commercial tuber rate by 85.82%, overall tuber yield by 28.38%, starch content by 34.85%, and vitamin C content by 30.79%, while reducing sugar levels decreased by 9.35%.ConclusionFaba bean-potato rotation (T2) effectively mitigated the adverse impacts caused by continuous potato cropping by altering the rhizosphere microbial structure and enhancing microbial functional pathways related to nutrient cycling. This study provides a detailed metagenomic perspective on the microbial mechanisms underlying the benefits of crop rotation and offers a theoretical basis for developing microbiome-informed ecological management strategies to mitigate continuous cropping obstacles in potato production on the Loess Plateau.